Thermal requirements for egg development of two endemic Wiseana pest species (Lepidoptera: Hepialidae) of economic importance. (30th March 2022) - Atijegbe, Sylvester R.; Mansfield, Sarah; Ferguson, Colin M.; Rostás, Michael; Worner, Susan P.
Abstract: Several endemic hepialid species in the genus Wiseana have become serious pests in New Zealand. Two species, in particular, reach high numbers, causing significant economic damage to pasture. Key developmental parameters for egg hatch for both species are needed along with monitoring and weather data to estimate the optimal time to apply control measures to the vulnerable early instar larvae. In this study, thermal requirements for the egg stage of Wiseana copularis and W . cervinata were determined to provide the basis of a prototype phenology model designed to improve the timing of application, therefore, the efficacy of an insect growth regulator, diflubenzuron, against early instar larvae. The standard linear regression method and the Ikemoto and Takai method of insect development were compared for the goodness of fit to the egg‐stage development of W . copularis and W . cervinata at constant temperatures to determine a developmental lower threshold ( T 0 ) and degree day (DD) requirement for the egg to the larval stage for each species. The Ikemoto and Takai method gave the highest estimate of T 0 for W . copularis at 7.9°C compared with 6.4°C for the standard regression method. For W . cervinata, the estimates ranged from 6.6°C (Ikemoto and Takai method) to 4.1°C (standard regression method). Of the two methods, the Ikemoto and Takai method had the better fit and lowest standard error for the parameters of interest. Thus, the Ikemoto and Takai model was chosen to estimate the critical parameters, T 0 and the requirement for egg‐larval development of W . copularis (7.9°C, 185 DD) and W . cervinata (6.6°C, 177 DD).